2013
DOI: 10.1088/1054-660x/23/2/025201
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of a general three-level atom interacting with a two mode

Abstract: A model of a three-level atom in the -configuration interacting with a two-mode field under a multi-photon process is considered. The effects of the mean photon numbers, detuning, Kerr-like medium parameters and various forms of the intensity-dependent coupling functional are considered. Analytical expressions for the time unitary operator, the density operator and the final state of the system are analyzed via the framework of the dressed states. The atom is prepared in its upper excited state, and the fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…For example, atom-photon entanglement in the interaction between a V-type three-level atom and single-mode cavity field in a Kerr medium with intensity-dependent coupling has been studied by Obada et al [19]. In addition, atom-photon entanglement in a Λ-type [20,21] and cascade [22] three-level atom interacting with a non-correlated two-mode cavity field has been investigated in the presence of Kerr nonlinearity. Furthermore, in the context of semi-classical theory of atom-light interaction, it has been shown that the induced steady state entanglement between an atom and its spontaneous emission can be controlled by intensity and detuning parameter of an applied field [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, atom-photon entanglement in the interaction between a V-type three-level atom and single-mode cavity field in a Kerr medium with intensity-dependent coupling has been studied by Obada et al [19]. In addition, atom-photon entanglement in a Λ-type [20,21] and cascade [22] three-level atom interacting with a non-correlated two-mode cavity field has been investigated in the presence of Kerr nonlinearity. Furthermore, in the context of semi-classical theory of atom-light interaction, it has been shown that the induced steady state entanglement between an atom and its spontaneous emission can be controlled by intensity and detuning parameter of an applied field [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, similar to references [20,21], we consider a  -type three-level atom that interacts with a non-correlated two-mode quantized field in a lossless cavity in the presence both Kerr and cross-Kerr nonlinearity. The atom-field coupling is assumed to possess some admissible intensity dependence.…”
Section: Introductionmentioning
confidence: 99%
“…A tentative approach to entanglement measures for a system of a three-level atom interacting with a quantized cavity-field has been introduced [36]. Furthermore, the evolution of the (atomic) field entropy for the threelevel atom one-mode [37][38][39][40][41][42][43][44] and two-mode [45,46] model has been studied. On the other hand, the system of a four-level atom interacting with a single mode of electromagnetic field has been studied [28,[47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, by paying attention to the negativity as a useful measure, the entanglement between the two atoms is studied in detail.As some important cases one may refer to intensity-dependent coupling [11,12], multi-mode field [13,14], multi-level atom [15,16] and multi-atom [17,18].In recent decades, a lot of attention has been particularly paid to the study of different configurations of a three-level atom (Λ, V and Ξ type) interacting with a single-and twomode fields with arbitrary detuning. Due to various usefulness of different types of three-level atomic systems in quantum optics and the quantum information processing (QIP) such as electromagnetically induced transparency (EIT) [19], coherent population trapping (CPT) [20] and quantum jumps [6], a lot of papers concern with the interaction between a three-level atom and the quantized field (see for instance [21,22,23,24,25,26]). The interaction between a Λ-type (V -type) three-level atom with a single-mode cavity field in a Kerr medium with intensity-dependent coupling has been studied in [21] ([22]).…”
mentioning
confidence: 99%